Iterative Metal Artifact Reduction in Head and Neck CT Facilitates Tumor Visualization of Oral and Oropharyngeal Cancer Obscured by Artifacts From Dental Hardware - Bayerl, Nadine; May, Matthias; Wuest, Wolfgang; Roth, Jessica; Kramer, Manuel; Hofmann, Christian; Schmidt, Bernhard; Uder, Michael; Ellmann, Stephan (Academic Radiology, 2023)
Rationale and Objectives: The purpose of this study was to evaluate the diagnostic utility of iterative metal artifact reduction (iMAR) in computed tomography (CT)-imaging of oral and oropharyngeal cancers when obscured by dental hardware artifacts and to determine the most appropriate iMAR settings for this purpose. Materials and Methods: The study retrospectively enrolled 27 patients (8 female, 19 male; mean age 64 ± 12.7 years) with histologically confirmed oral or oropharyngeal cancer obscured by dental artifacts in contrast-enhanced CT. Raw CT data were reconstructed with ascending iMAR strengths (levels 1/2/3/4/5) and one reconstruction without iMAR (level 0). For subjective analysis, two blinded radiologists rated tumor visualization and artifact severity on a five-point Likert scale. For objective analysis, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and artifact index (AI) were determined. Results: iMAR reconstructions improved the subjective image quality of tumor edge and contrast, and the objective parameters of tumor SNR and CNR, reaching their optimum at iMAR levels 4 and 5 (P < .001). AI decreased with iMAR reconstructions reaching its minimum at iMAR level 5 (P < .001). Tumor detection rates increased 2.4-fold with iMAR 5, 2.1-fold with iMAR 4, and 1.9-fold with iMAR 3 compared to reconstructions without iMAR. Disadvantages such as algorithm-induced artifacts increased significantly with higher iMAR strengths (P < .05), reaching a maximum with iMAR 5. Conclusion: iMAR significantly improves CT imaging of oral and oropharyngeal cancers, as confirmed by both subjective and objective measures, with best results at highest iMAR strengths.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Artifact; Cancer imaging; Computed tomography; Head and neck; Metal artifact reduction